First Record of Epizoic Diatom Presence on Poricellaria ratoniensis (Bryozoa, Cheilostomata) from Java Sea, Indonesia - Meezan Ardhanu Asagabaldan; Rhesi Kristiana; Diah Ayuningrum; Adib Mustofa; Ika Agus Rini (Journal of Science and Applicative Technology, 2023)
Indonesian waters cover a high diversity of marine organisms (micros- and macros-) of interest to scientists. Among this diversity, the neglected bryozoan had been scarcely reported due to lack of information from this area, especially on the epizoic diatoms since they are favorable as their dietary. This preliminary study aimed to investigate and witness the presence of epizoic diatom on bryozoan Poricellaria ratoniensis. Our data revealed an assemblage of diatoms attached to bryozoan surfaces and exhibiting taxonomic diversity. In total, members of five genera Amphora, Cocconeis, Neodetonia, Staurophora, and Thalassiosira were found, including the measurement of their cell size, respectively. The attached diatoms were mainly within the bryozoan operculum (op) range, functioning as feeding organs. However, further study is needed to understand the interaction between bryozoan and diatoms aiming for ecological services.